Lead sortion study in weathered soils in its different fractions (Research, Society and Development, 2020)
Among the toxic metals soil accumulation processes, such as lead (Pb), adsorption is one of the most noticed. For soils, adsorption is the passage of a solute from the aqueous phase to the solid adsorbent surface. Considering that the soil adsorption isotherms often vary strongly from soil to soil, more detailed studies of the metals behavior in Brazilian soil are necessary, in order to better adapt the models to Brazilian climatic and environmental conditions. Thus, the objective is to study the lead adsorption (Pb) in a Red-Yellow Latosol (RYL) and a Red-Yellow Argisol (RYA) and its different granulometric fractions. To determine the ratio between the amount of a compound adsorbed from solutions at various concentrations and the amount remaining in these solutions, adsorption isotherms are generated which gives quantitative results. The coefficient of distribution (Kd) of the metal by the soils and their different fractions was also calculated. In this study, it was possible to verify that the higher adsorption of Pb+2 was observed by the silt + clay soil fraction, according to the isotherms. As for the classification of the isotherms, the RYA presented the type L isotherm and the RYL the type H. From the values of Kd it is noticed that the lead has a high affinity for the RYA and low affinity for the RYA. In conclusion, the Freundlich model was well suited to the experimental results of lead adsorption by soils.